Analisis Pengaruh Citra Merek dan Kualitas Layanan Terhadap Kepercayaan Pelanggan dan Implikasinya Terhadap Keputusan Pembelian Produk Pada Optik Gajahmada Semarang - Ulya, Nadia Nailil; Tri Astuti, Sri Rahayu (Faculty of Economics and Business Diponegoro University, 2016)
The purpose of this research is to know how the influence of the brand image and quality of service towards customer trust and its implication to purchasing decisions product in Gajahmada Optical Semarang.CompetitionÂ in the Optical world becomes more intense, each Optical required to have a competitive advantage to win the competition and survive in the market. This study aims to investigate the influence of brand image and quality of service for customer trust and its implications for purchasing decisions product in Gajahmada Optical Semarang.The sample in this research wereglasses users in Semarang who already buy a product at Gajahmada Optical Semarang. The samples were 100 people selected using purposive sampling through an offline and online questionnaire. Analysis of the data used in this research are validity and reliability, the classic assumption test, multiple regression analysis, goodness of fit test. The results of the multiple linear regression analysis is, Y1= 0,279 X1 +0,633 X2 and Y2 = 0,726 Y1. The most influential independent variable towards the dependent variable is customer trust (0,726), followed by quality of service (0,633), and the last one is brand image (0,279). T test results showed that the brand image,quality of service,customer trust Â have a positive and significant influence towards purchasing decision. The coefficient of determination obtained from the independent variable in this research is 52,2%, while the remaining 47,8% is influenced by other variables outside the model of this research.